Research on digital twin based temperature field monitoring system for LNG storage tanks. (30th June 2023) - Wu, Yujian; Sun, Jiangang; Yang, Gang; Cui, Lifu; Wang, Zhen; Wang, Mengzhu
Highlights: Digital twin technology is used to realize LNG tank temperature-field digital monitoring. A digital twin framework including data, model, and application layers is established. A twin model realizes inversion from local sensing data to the overall temperature field. A digital platform is built to visualize temperature field monitoring and locate leaks. Abstract: The temperature distribution is a critical indicator of the health condition of liquefied natural gas (LNG) storage tanks. Point measurements are the main method of traditional LNG tank temperature field monitoring. To obtain more abundant temperature data and realize the digital transformation of temperature field monitoring, an LNG tank temperature field monitoring system was constructed, which consists of a model layer, a data layer, and an application layer, by combining sensing data with digital twin (DT) technology. First, the temperature distribution of the LNG storage tank under working and leaking conditions was simulated, and the sensing monitoring network was constructed by combining Fiber Bragg Grating (FBG) sensor temperature-sensing experiments. Second, a finite element calculation model of the steady-state temperature field of an LNG storage tank was developed, and the twin model was generated by fusing the sensing data to realize the inversion from local sensing data to the whole temperature field. Finally, an LNG temperature field monitoring system based on the DT was constructed. Based on physical field leakage simulations performed with the Fluent software, the functions of visual interaction, construction splitting, temperature chart analysis, leakage diagnosis, and historical data management of the twin models were realized, which provided system building samples for digital monitoring of new LNG storage tanks.